Manajemen Risiko Berbasis Maqasid Syariah Sebagai Strategi Keberlanjutan Bank Syariah Di Indonesia: Kajian Literatur - Dewi Risyantika; Laili Fathul Hidayah; Reska Maulida; Riyan Damara Putra; Ridwansyah Ridwansyah; Wan Ruslan Abdul Ghani (JPSDa: Jurnal Perbankan Syariah Darussalam, 2026)
This study aims to systematically review the integration of maqasid al-shariah into Islamic bank risk management and to develop a conceptual framework linking Shariah values, risk categories, governance, and sustainability. The study employs a Systematic Literature Review (SLR) approach following the PRISMA guidelines. Data were collected from Scopus, Web of Science, and Google Scholar using combinations of the keywords "maqasid al-shariah," "Islamic banking," "risk management," "Shariah governance," and "sustainable finance" with the Boolean operators AND and OR. The review was limited to peer-reviewed articles published in English between 2015 and 2026. Of the 135 records initially identified, 105 remained after duplicate removal, 45 articles were assessed through full-text screening, and 15 studies met the inclusion criteria for the final synthesis. The selected studies were analyzed using thematic analysis to identify major themes, research gaps, and conceptual relationships among the variables. The findings reveal that maqasid al-shariah has predominantly been employed as a normative framework for performance evaluation rather than as an operational foundation for risk management. The literature on financial risk, Shariah compliance risk, digital risk, governance, and sustainability also remains fragmented. Furthermore, no comprehensive model has explicitly translated the objectives of maqasid al-shariah into the processes of risk identification, measurement, mitigation, and monitoring. This study proposes an integrative maqasid-based risk governance framework that positions the protection of religion (hifz al-din), wealth (hifz al-mal), life (hifz al-nafs), intellect (hifz al-'aql), and progeny (hifz al-nasl) as the ethical foundation of Islamic bank risk management. The findings provide practical implications for regulators, Shariah Supervisory Boards, and Islamic bank management in developing risk management systems that are more equitable, accountable, and sustainable.